Using Biological Elicitation to Improve Type 2 Diabetes Targeted Food Quality of Stored Apple - Ankolekar, Chandrakant; Sarkar, Dipayan; Greene, Duane; Shetty, Kalidas (Frontiers in Sustainable Food Systems, 2021)
Food quality improvements of fresh fruits targeting both food preservation and human health is essential to advance healthy dietary options and to mitigate imbalanced nutrition-linked non-communicable chronic disease (NCDs) challenges globally. Specifically, protective phenolic bioactives of fruits with dual functional benefits can be harnessed to advance innovations for improving nutritional quality and post-harvest shelf-life of perishable fruits. Based on this rationale the dual functional benefits of plant phenolics were harnessed using novel biological elicitation strategies to modulate phenolic bioactive-linked protective responses in apple during storage in two interrelated studies. Bioprocessed food-grade elicitors [water soluble chitosan oligosaccharide-(COS) and phenolic enriched oregano extracts-(OX)] were targeted as post-harvest dipping treatments (2 & 4 g/ L) and compared with diphenylamine (DPA) (1 & 2 g/L) to enhance phenolic-linked antioxidant and anti-diabetic (type 2 diabetes) relevant properties of Cortland apple during 3-months of storage (4°C). The selection of bio-elicitors and respective doses were based on the foundations of the previous related study, which resulted in reduction of superficial scald of Cortland apple during storage. Apples sampled over 3-months as aqueous and ethanol (12%) extracts of peel and pulp were analyzed separately for total soluble phenolic content, phenolic profile, antioxidant activity, and glucose metabolism relevant α-amylase and α-glucosidase enzyme inhibitory activities using in vitro assay models. Enhanced soluble phenolic content and associated antioxidant activity were observed in ethanol (12%) extracts of apple peel with 4 g/L COS elicitor treatments after 2- and 3- months of storage. High chlorogenic acid and quercetin derivatives were found in peel extracts of Cortland apple, while pulp extracts had high chlorogenic and gallic acids. Additionally, high α-glucosidase enzyme inhibitory activity, which is relevant for managing post-prandial hyperglycemia of type 2 diabetes was also observed in bio-elicited apple peel and pulp extracts. Therefore, results of these two interrelated studies indicate that bioprocessed food grade elicitor such as OX and COS can be recruited as a novel tool to enhance protective phenolic responses for improving type 2 diabetes targeted food quality and post-harvest storage quality of apple.